Succession Planning For Family Business Sustainability - Fadlilah, Lilik Tanwirotul; Sholikha, Akhris Fuadatis; Muarrifah, Safrina; Mubarok, Husni; Lesmana, Hendra (Wealth: Journal of Islamic Banking and Finance, 2024)
Although family businesses play a big part in Indonesia's economy, many of them do not continue into the next generation. Family businesses have several challenges, namely the lack of awareness regarding the importance of sustainability, the existence of myths related to differences in the successor generation also determines the sustainability of the business so that the existence of succession is a phenomenon of changing generations where the sustainability of the family business will be left to the sustainability of the company that guarantees it. This study examines the effect of succession planning on family business sustainability, with a focus on MSMEs in the Banyumas and Tegal regions. Quantitative methods were used to analyze data obtained through questionnaires from business owners. The simple regression results show, with an independent variable contribution of 86.9% to explain family business sustainability. This means that succession planning significantly improves the sustainability of businesses the variability of sustainability can be explained by 86.9% by succession planning. This study emphasizes the importance of education and training for the next generation as well as transparency in communication between owners and successors. The findings are expected to be a reference in passing on the family business with careful planning to ensure business sustainability. Suggestions for future research include expanding the scope of the business and using more varied research methods.